The Role of Firm Attributes in Financial Distress Risk - Raharjo, Yulianti; Fitriani, Nurul (Journal of Economics, Business, and Government Challenges, 2024)
This study explores the role of firm attributes consisting of corporate reputation, firm size, leverage, financial slack, and depreciation on the financial distress risk. The sample includes 1,789 non-financial public companies listed on the Indonesia Stock Exchange (BEI) during the period 2021 to 2023. Multiple regression analysis using STATA application to test the proposed hypotheses. The findings suggest that companies with a good reputation and high liquidity tend to have a lower risk of financial distress. In contrast, companies with larger sizes, higher leverage, and higher depreciation levels are associated with an increased risk of financial distress. This study expands understanding of the factors affecting financial distress risk, focusing on the financial aspects of companies. Furthermore, the findings are expected to provide useful insights for management regarding the importance of firm attributes (such as corporate reputation, firm size, leverage, financial slack, and depreciation) in managing financial distress risk, especially following the economic impact of the COVID-19 pandemic.